HLA-G expression in peritumoral fundic gland mucous neck cells, but not in tumor lesions, related to poor survival in patients with gastric cancer - Zhang, Xia; Han, Qiu-Yue; Zhang, Jian-Gang; Yan, Wei-Hua; Lin, Aifen (Frontiers in Immunology, 2025)
IntroductionThe concept that human leukocyte antigen-G (HLA-G) expression is specifically in various malignant lesions but absent in adjacent normal tissues has been well documented, and HLA-G is acknowledged as a novel immune checkpoint.MethodsIn this study, HLA-G expression in 523 gastric cancer (GC) lesions and 283 case-matched peritumoral tissues (PTTs) was analyzed by immunohistochemistry. The clinical significance of HLA-G expression in GC lesions and case-matched PTTs was evaluated, and a specific HLA-G-positive subpopulation in PTTs was identified.ResultsData showed that HLA-G expression was significantly different between GC lesions (370/523, 70.7%) and PTTs (238/283, 84.1%; p<0.001). HLA-G in GC lesions was more frequently observed in older patients (76.2% vs. 65.3%, p=0.006), and HLA-G in PTTs was more commonly observed in female patients (92.0% vs. 80.5%, p=0.014). Survival analysis revealed that HLA-G expression in PTTs (overall survival: 42.0 months vs. 56.7 months, p=0.023), but not in GC lesions (52.1 months vs. 50.9 months, p=0.623), is significantly associated with poor prognosis. The fundic gland mucous neck cells were the only subpopulation that expressed HLA-G.DiscussionOur findings, for the first time, suggest that fundic gland mucous neck cell HLA-G expression in PTTs is associated with GC progression.